The study of thermal interaction and microstructure of sodium silicate/bentonite composite under microwave radiation - Subannajui, Kittitat (Materials chemistry and physics, 2016)
The commercial heating oven usually consumes the power around 2500–3000 Watt and the temperature inside the oven is still below 350 °C. If we need to increase a temperature above 500 °C, a special heating setup with a higher power furnace is required. However, in this work, we propose a composite material that interacts with 2.45 GHz 500 Watt microwave and rapidly redeems the thermal energy with the temperature around 600–900 °C. The composite amorphous material easily forms liquid ceramics phase with a high temperature output and responds to the microwave radiation better than that of the solid phase. During the heating process, phase transformation occurs. This method is very effective and can be used to drastically reduce the power consumption of any heating process. •Amorphous phase transforms to liquid phase by microwave radiation.•Pure sodium silicate and pure bentonite cannot show temperature overshoot.•Silicate-bentonite composite shows a high temperature overshoot above 700 °C.•A rapid heating crucible for the annealing application is fabricated.